Development of a health dialogue model for patients with diabetes: A complex intervention in a low-/middle income country. (2018) - Reid, M.; Walsh, C.; Raubenheimer, J.; Bradshaw, T.; Pienaar, M.; Hassan, C.; Nyoni, C.; Le Roux, M.
Abstract: Type 2 diabetes is reaching epidemic proportions in a low-/middle income country such as South Africa, where most patients are managed in the public health sector with limited resources. Poor knowledge, negative attitudes and unhealthy practices are common, highlighting the need for healthcare providers to adapt health communication strategies appropriately. The current study aimed to develop a health dialogue model by applying a multiple-methods design informed by the United Kingdom Medical Research Council's guidelines for the development and evaluation of complex interventions. Guided by this framework, four separate but inter-related studies were conducted to establish the active components of health dialogue. Participants included patients with type 2 diabetes from a variety of public healthcare settings and healthcare providers who provide services to them. The findings from the four primary studies were then synthesised at a two-day workshop during which three focus areas emerged, including the community, the patient and the healthcare provider. Community awareness could be raised by delivering key messages in the native tongue of patients through combinations of traditional folk media such as drama and storytelling in the waiting rooms of health centres. Self-management of patients could be promoted by active participation of patients in tailored health communication using peer support and the use of mobile health devices. Finally, training platforms for healthcare providers should include in-service training through interactive workshops. Our culturally sensitive health dialogue model has the potential to improve adherence to treatment, leading to greater satisfaction and consequently improved health outcomes.